Rancang Bangun Sistem Kendali Suhu Ruangan Menggunakan Metode Fuzzy - Ria Darma Pratama; Anggia Dasa Putri (Computer Science and Industrial Engineering, 2024)
The development of technology is getting faster every day, many technologies are used in many fields. The number of new technologies that appear. Innovations made using current technology can ease human work rather than having to be done manually. This research discusses the Design of a Room Temperature Control System Using the Fuzzy Method. The purpose of designing this tool is to control the temperature in the room and is designed in the form of a prototype. With the Fuzzy Mamdani method, this tool can help make human work lighter. This room temperature control uses an Arduino Uno microcontroller, I2C LCD to show the temperature and the number of people in the room, DC Motor Driver as a fan speed regulator, Infrared Sensor to detect people entering and leaving the room, DHT11 Sensor to detect temperature and Fan as a room temperature controller. If the number of people is large and the temperature is getting hotter in the room then, the fan can work to cool the room. The software used in this research is Arduino IDE. Based on the research results, this room temperature control can work effectively.